Pengaruh Tipe Kepribadian (Extrovert & Introvert) Terhadap Prestasi Belajar Matematika Kelas VIII SMP Negeri 7 Mataram - Buja Marsah, Ratna; Sridana, Nyoman; Kurniawan, Eka (Griya Journal of Mathematics Education and Application, 2025)
This study aims to determine the influence of personality types on mathematics achievement among secondary school students. The personality types examined include extrovert and introvert. The research used an ex post facto design with a quantitative approach. The sample consisted of 39 students, divided into two groups based on the results of a personality test: 23 extrovert students and 16 introvert students. Mathematics achievement data were obtained from previously validated mathematics test scores. Data analysis was conducted using an independent samples t-test to determine the difference in average achievement between the two personality types. The results showed a significant difference in mathematics achievement between extrovert and introvert students, with introvert students achieving a higher average score (77.56) compared to extrovert students (66.43). The conclusion of this study is that personality type affects mathematics achievement. Therefore, it is important for teachers to consider students' personality characteristics when designing effective learning strategies.